To Broach the Conscious Pain with a Word. The Thematization of Disease and Death in the Last Poems by Jacek Kaczmarski - Szkaradnik, Katarzyna (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
A singer and bard Jacek Kaczmarski left a poetical record of his coping with esophagus cancer in thepoems comprised in the posthumous volume entitled Tunnel. In this article, on the background of “thediscourse of disease”, the authoress analyses some of the works placed in that book to see how the illness and the end of life are conceptualized in them as well as considers the functions of definite poeticalmeasures exposing experience of the disease. Furthermore, she presents how the social observationsrelating to the surroundings of suffering person are introduced. Nevertheless, the main object of thoughtin this text are the ways of taming or else “disarming” of cancer and death by means of carnivalization,removing the taboo, the trial with the myths grown around - but not only. On the one hand, it is aboutstrategies of grotesque transforming, caricature, naturalism, but on the other hand their basis is created byauthentic, dramatic experiences resulting in such moving works as the title Tunnel, a trial of explicationof clinical death. The authoress ponders over a bond of such polar attitudes and poetics — the brutalityor frivolousness of imaging with pathos and lyricism. She tries to outline the ars moriendi of Kaczmarski,based on humanistic protest in the face of death fatality, apologue of temporality, identity and on theTale. That “art of dying” shows how to meet the inevitable, not only worthily, but also cheerfully.